An Inventory Model deteriorating itemswith Demand Dependent Production Rate under Permissible Delay Payment - Neeraj Kumar, Sweta Dahiya, Sanjey Kumar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This paper considers a single supplier offering trade credit to demand a dependent production rate with ramp type demand, which has not been reported in the literature. Previously, two inventory models have been developed under the above conditions.Secondly, order quantity and replenishment cycle time algorithms are designed to be optimized. Thefindings of the above study show that lowering the production rate, decreasing the order insertion frequency and decreasing the production rate leads to cost reduction, with no effect on the optimal solution as well as demand-dependent production rates.The retailer will cut the replenishment cycle when the growth time is higher than the business loan; when it is small, within the maturity period of the goods, the optimal order cycle and the quantity of the optimal quantity will have no effect on the trade credit. Finally, numerical examples are discussed to demonstrate sensitivity analysis of optimal solutions.